2018
DOI: 10.3389/fmicb.2018.01229
|View full text |Cite
|
Sign up to set email alerts
|

Cultivable Microbial Diversity Associated With Cellular Phones

Abstract: A substantial majority of global population owns cellular phones independently to demographic factors like age, economic status, and educational attainment. In this study, we investigated the diversity of microorganisms associated with cellular phones of 27 individuals using cultivation-based methods. Cellular phones were sampled using cotton swabs and a total of 554 isolates representing different morphotypes were obtained on four growth media. Matrix-assisted laser desorption ionization time of flight (MALDI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…In study of Kurli R. et al [ 32 ], matrix-assisted laser desorption ionization time of flight (MALDI-TOF) mass spectrometry was used to generate protein profiles for 527 isolates obtained from cellular phones by swabs. A dendrogram was constructed based on the protein profiles of the remaining isolates, to group 112 isolates under 39 different proteotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In study of Kurli R. et al [ 32 ], matrix-assisted laser desorption ionization time of flight (MALDI-TOF) mass spectrometry was used to generate protein profiles for 527 isolates obtained from cellular phones by swabs. A dendrogram was constructed based on the protein profiles of the remaining isolates, to group 112 isolates under 39 different proteotypes.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing interest in studying forensically relevant microbial profiles left behind on objects and surfaces. For instance, several studies showed that there is often a high level of bacterial presence on personal objects such as mobile phones ( Koroglu et al, 2015 ; Kõljalg et al, 2017 ; Koscova et al, 2018 ; Kurli et al, 2018 ). Furthermore, human-associated items such as shoes and mobile phones have been shown to support distinct microbiomes ( Lax et al, 2015 ; Coil et al, 2019 ).…”
Section: Major Themes In the Forensic Microbiology Literaturementioning
confidence: 99%
“…Therefore, agreement between MALDI-TOF MS-based biotyping and 16S rRNA gene sequencing was observed to be limited. While the emerging MALDI biotyping is being popular in different fields of microbiology that has partly replaced conventional biochemical identification methods [12], variability of this methodology for the identification of microbes has been attributed to factors such as sample processing methods, matrix solutions, spectral quality, and data analysis methods [6,21]. The methodology is becoming more popular in clinical set-ups for speedy and low-cost microbial identification [28,34] and also in the analysis of bioactive compounds [46].…”
Section: Comparative Assessment Of Psychrotolerant Bacteria Using 16smentioning
confidence: 99%